2001
DOI: 10.1099/00207713-51-2-603
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomonas cloacae sp. nov., a nonylphenol-degrading bacterium isolated from wastewater of a sewage-treatment plant in Tokyo.

Abstract: A nonylphenol-assimilating bacterium isolated at a sewage-treatment plant in Tokyo was studied phenotypically, genotypically and phylogenetically. Analysis of the 16S rDNA sequence, the GMC content of the DNA (63 mol %) and the isoprenoid quinone composition, as well as the presence of sphingoglycolipid and the whole-cell fatty acid profile, revealed that the isolate is a member of the genus Sphingomonas. However, the sequence similarity of the 16S rDNA with that of known Sphingomonas spp. was found to be at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
60
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…Alternatively, nonylphenol isomers with highly branched alkyl chains initially may be attacked via hydroxylation of the phenolic ring. This has been proposed for bacterial isolates belonging to the genera Pseudomonas, Stenotrophomonas and Sphingomonas (Corvini et al, 2004;de Vries et al, 2001;Fujii et al, 2000Fujii et al, , 2001Soares et al, 2003;Tanghe et al, 1999), and intracellular monooxygenases have been proposed to be responsible for aromatic hydroxylation in Pseudomonas and Sphingomonas (de Vries et al, 2001;Soares et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, nonylphenol isomers with highly branched alkyl chains initially may be attacked via hydroxylation of the phenolic ring. This has been proposed for bacterial isolates belonging to the genera Pseudomonas, Stenotrophomonas and Sphingomonas (Corvini et al, 2004;de Vries et al, 2001;Fujii et al, 2000Fujii et al, , 2001Soares et al, 2003;Tanghe et al, 1999), and intracellular monooxygenases have been proposed to be responsible for aromatic hydroxylation in Pseudomonas and Sphingomonas (de Vries et al, 2001;Soares et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The t-NP isomers with the more branched side chains are assumed to be more resistant to biodegradation than those with the less branched nonyl chains or 4-n-NP (Lalah et al, 2003;Tanghe et al, 1999). As yet, only a few bacterial pure cultures capable of utilizing chain-branched nonylphenols as growth substrates have been described (Corvini et al, 2004;de Vries et al, 2001;Fujii et al, 2000Fujii et al, , 2001Soares et al, 2003;Tanghe et al, 1999), while one yeast has been reported to grow on 4-n-NP (Vallini et al, 2001). …”
mentioning
confidence: 99%
“…nov., respectively, according to the scheme of Takeuchi et al (2001). The reclassification of Sphingomonas cloacae (Fujii et al, 2001) has already been taken up by O. Prakash & R. Lal (unpublished). The reclassification of 'Sphingomonas agrestis' has not been undertaken as it is not a species with a validly published name.…”
mentioning
confidence: 99%
“…This feature is known to hamper microbial degradation 16,17) . Recently Tanghe et al 30) and subsequently Fujii et al 5,6) described the isolation of Sphingomonas strains able to grow on a commercial mixture of branched NP isomers as a sole carbon and energy source in pure culture. Until now, there have been only vague indications as to how branched NP molecules are attacked by bacteria 6,13,30) .…”
mentioning
confidence: 99%